Tinjauan Yuridis Terhadap Kasus Mafia Tanah di Dago Elos - Tjandra, Sheren Michi; Nabila, Irene Rakha; Ely, Claureria Angie (Universitas Pahlawan Tuanku Tambusai, 2025)
The modus operandi used by the land mafia in Dago Elos involves falsifying documents and land certificates. The main perpetrators, the Muller brothers, falsified a number of land documents to deceive residents, even using documents claimed to be from before Indonesian independence. As a result, they managed to take control of land that was actually owned by local residents. This study uses the library research method, which aims to study and analyze various written sources that are relevant to the legal issues related to the land mafia case in Dago Elos. This method emphasizes the collection of secondary data from various literature, laws and regulations, journals, books, articles, and previous research that can provide a comprehensive picture of the legal aspects related to the land mafia problem. Based on the Decision of the Bandung District Court Number 601/Pid.B/2024/PN Bdg regarding the land mafia case that occurred in Dago Elos, the defendants Heri Hermawan Muller and Dodi Rustandi Muller were proven legally and convincingly to have committed the crime of falsifying documents as regulated in Article 266 paragraph (2) of the Criminal Code in conjunction with. Article 55 paragraph (1) 1 of the Criminal Code.